Preliminary study on fungi diversity at UiTM Pahang / Norawiah Ibrahim - Ibrahim, Norawiah (Faculty Of Applied Sciences, 2017)
Fungus is an organism that cannot manufacture its own food but obtains its food and energy by taking in organic substances, usually plant. There are many fungi species that can be found in the ecosystem but some of them have not been identified and studied for further research. The purposes of this study were to identify the species of fungi that grow on forest and oil palm plantation, to compare the diversity of fungi on two different areas and to determine the abiotic factors affecting the growth of fungi on the study areas. This study focused on two locations in UiTM Pahang; reserved forest and oil palm plantation. The fungal samples were collected at both locations in six quadrates for each location. Four abiotic parameters such as soil pH, relative humidity, light intensity and temperature were measured at both locations. 24 samples were collected at the reserved forest and oil palm plantation. Seven species and ten genera were identified at the reserve forest while five species and two genera identified at the oil palm plantation. The results showed that there are more species and genera of fungi that grow at reserved forest compared to oil palm plantation. The reserve forest provides the conditions and environment that are suitable for fungi to grow and survive. The abiotic parameters significantly affect the growth and diversity of fungi in both locations. It is recommended to increase the number of parameters and use high technology equipments to improve the accuracy in assessing fungi diversity and identification.